Histone Deacetylases in the Pathogenesis of Diabetic Cardiomyopathy - Ke, Xiangyu; Lin, Zhirui; Ye, Zebing; Leng, Meifang; Chen, Bo; Jiang, Chunjie; Jiang, Xiaoyun; Li, Guowei (Frontiers in Endocrinology, 2021)
The global burden of diabetes mellitus and its complications are currently increasing. Diabetic cardiomyopathy (DCM) is the main cause of diabetes mellitus associated morbidity and mortality; therefore, a comprehensive understanding of DCM development is required for more effective treatment. A disorder of epigenetic posttranscriptional modification of histones in chromatin has been reported to be associated with the pathology of DCM. Recent studies have implicated that histone deacetylases could regulate cardiovascular and metabolic diseases in cellular processes including cardiac fibrosis, hypertrophy, oxidative stress and inflammation. Therefore in this review, we summarized the roles of histone deacetylases in the pathogenesis of DCM, aiming to provide insights into exploring potential preventative and therapeutic strategies of DCM.